The Turkish version of the 5-item dry eye questionnaire (deq-5): translation, validity and reliability - BAĞATUR VURGUN, ELİF (My University, 2021)
THE TURKISH VERSION OF THE 5-ITEM DRY EYE QUESTIONNAIRE (DEQ-5): TRANSLATION,VALIDITY AND RELIABILITYAim: To evaluate the reliability and validity of Turkish translation of the original 5-item Dry EyeQuestionnaire (DEQ-5) and to compare the DEQ-5 with the Ocular Surface Disease Index (OSDI)questionnaire, tear break-up time (TBUT), corneal staining, and Schirmer test results.Methods:The linguistic validation procedures adopted internationally, including forward translations, backwardtranslation into English, examination of the translation quality, and a pilot test on ten patients. Onehundred subjects were recruited for the study. The translated validated questionnaire was applied to 25subjects two-time points (second time within three days) to evaluate the intra-test reliability. Subjects alsocompleted the OSDI questionnaire and an ophthalmic examination, including Schirmer tests, TBUT, andcorneal staining. Receiver operating characteristics (ROC) were assessed to obtain sensitivity andspecificity of the Turkish version of the DEQ-5.Results:The mean age of subjects was 45.7±16.2 years, and 65% of subjects were female. Overall, the test-retestreliability was excellent with an intra-class correlation coefficient value of 0.95 (95% CI 0.90–0.98, p <0.001). The Cronbach’s s alpha reliability coefficient was 0.90, which demonstrated an excellent degreeof internal consistency of the DEQ-5. Using ROC analyses to compare the results of the DEQ-5 with theresults of the OSDI, the area under the curve was found 0.95, which means an excellent predictor todiscriminate patients with dry eye. According to the ROC curve analysis, the optimum cut-off thresholdwas found 6 with an 81% sensitivity and 91% specificity. When the diagnosis was established based onthe positive OSDI (>13) and at least one positive sign (TBUT and/or corneal staining), the sensitivity andspecificity based on the cut-off threshold of 6, were 87% and 95%, respectively.Conclusion: The Turkish version of the DEQ-5 is a valid and reliable questionnaire and capable ofdifferentiating patients with dry eye.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE